A Case Study on the Deformation of Metro Foundation Pit in Silt Stratum in North China - Yonggang Zhang; Yonghong Wang; Yuanyuan Zhao (Shock and Vibration)
Geological conditions of urban subway foundation pits are controllable factors in determining the deformation of pits. In this paper, the monitoring data and statistical data of a subway deep foundation pit in North China are presented and compared with those of Tianjin subway. The deformation characteristics of the proposed pit, open excavated with triple-layer steel supports, are introduced in detail. Based on the aforementioned information, the energy conservation equation of the mobilized strength design (MSD) method in which the compression deformation energy of internal support is considered is applied to predict the maximum lateral movement. The maximum lateral movement turns out to be 22.2 mm according to the improved MSD method, which is very close to the measured value.